The Influence of Parental Involvement, Teacher, and Peer Support on Mastery Goal Orientation and Self-Efficacy among Vocational High School Students - Laka, Laurensius (SAPA - Jurnal Kateketik dan Pastoral, 2020)
English: In order to exchange views, products, ideas, and culture, nations are encouraged to live interdependently. Countries that master science and technology likely take advantage of such exchanges. But although Indonesia is rich in natural resources and has a large population, the education in Indonesia has not shown significant progress. Educational policies for Vocational High School (SMK) students are relatively unique, because students are prepared both to enter the workforce, and to pursue a higher knowledge in university. According to theorists, in such an environment, students need self-regulated learning (SRL). Menurut teoretisi, dalam kondisi seperti itu, siswa membutuhkan self-regulated learning (SRL). Theoretically, the SRL strategies of students are influenced by a motivation component, which includes mastery goal orientation (MGO) and self-efficacy. Student motivation is influenced by their perception of their social environment (parental involvement, peer support, and teacher support). The purpose of this study was to investigate the influence of parental involvement, teacher and peer support on mastery goal orientation and self-efficacy among Vocational High School students in Pasuruan, Indonesia. To achieve these objectives, this study was designed using a quantitative approach, with survey research methods. The instrument used was a questionnaire filled out by a sample of 500 students. The analysis applied to examine the hypothesis in this study was structural equation modeling (SEM) based on the variance, namely partial least squares (PLS). Findings showed that parental involvement, peer support, and teacher support were positive predictors of mastery goal orientation (MGO). Parental involvement, peer support, teacher support, and MGO were also positive predictors of self-efficacy. Indonesia: Adanya pertukaran pandangan, produk, pemikiran, dan unsur-unsur budaya telah mendorong bangsa-bangsa di dunia untuk hidup saling tergantung. Bangsa-bangsa yang menguasai ilmu pengetahuan dan teknologi berpeluang mengambil keuntungan dari pola interaksi semacam itu. Sayangnya, Indonesia dianugerahi sumber daya alam dan penduduk yang besar, tetapi dunia pendidikan Indonesia belum menunjukkan kemajuan yang berarti. Menyoroti pendidikan pada jenjang menengah, kebijakan untuk siswa Sekolah Menengah Kejuruan (SMK) relatif unik, sebab siswa disiapkan untuk bekerja sesuai dengan keahliannya, tetapi pada saat yang sama, pengetahuan siswa juga diperluas agar dapat melanjutkan ke jenjang perguruan tinggi. Menurut teoretisi, dalam kondisi seperti itu, siswa membutuhkan self-regulated learning (SRL). Tujuan dari penelitian ini adalah untuk mengetahui pengaruh keterlibatan orang tua, guru dan dukungan teman sebaya terhadap mastery goal orientation dan self-efficacy pada siswa SMK di Pasuruan, Indonesia. Untuk mencapai tujuan tersebut, penelitian ini dirancang dengan menggunakan pendekatan kuantitatif, dengan metode penelitian survei. Instrumen yang digunakan adalah angket yang diisi oleh sampel sebanyak 500 siswa. Analisis yang digunakan untuk menguji hipotesis dalam penelitian ini adalah Structural Equation Modelling (SEM) berbasis varians yaitu partial least squares (PLS). Temuan menunjukkan bahwa keterlibatan orang tua, dukungan teman sebaya, dan dukungan guru adalah prediktor-prediktor positif dari mastery goal orientation (MGO). Keterlibatan orang tua, dukungan teman sebaya, dukungan guru, dan MGO juga merupakan prediktor positif dari self-efficacy.